Host genomics of COVID-19: Evidence point towards Alpha 1 antitrypsin deficiency as a putative risk factor for higher mortality rate. (February 2021) - Dutta, Atanu Kumar; Goswami, Kalyan
Abstract: Corona Virus Disease 2019 (COVID-19) has emerged as a pandemic leading to unprecedented disruption of global health and economy. Transmembrane protease serine 2 (TMPRSS2) has been found to be critical in priming the viral spike protein and the host ACE2 receptor before the virus enters into the host cell. Recent studies have experimentally demonstrated that Alpha 1 antitrypsin (encoded by SERPINA1 gene) is an inhibitor of TMPRSS2 and provided support to the already approved therapy as a candidate for COVID-19. Interestingly Alpha 1 antitrypsin deficiency is common among Europeans. Here we have provided in silico evidence that Alpha 1 antitrypsin can interact with TMPRSS2 and both of them are co-expressed in the human liver and lung. We then analyzed the gnomAD dataset to show that Europeans and Latinos have a substantially higher carrier frequency of Alpha 1 Antitrypsin Deficiency (~12%) compared to other large ethnicities. Therefore, we hypothesize that Alpha 1 antitrypsin deficiency might be a risk factor for severe infection with SARS-CoV-2. We propose Alpha 1 antitrypsin status as a potential prognostic predictor of COVID-19 outcome.